Building Supply Chain Leaders in Creating Business Performance: A Rasch Model Approach - Herlina, Maria Grace; Lasmy, Lasmy; Sudrajat, Darjat; Syahchari, Dicky Hida; Saroso, Hardijanto (International Journal of Supply Chain Management, 2020)
The logistics and supply chain is an emerging business in the world. As the "network" business process, the supply chain business depends on the critical success factor that is human resources. This research is conducted using the Rasch Model Approach to examine the supply chain employees in the telecommunication industry in Indonesia. The supply chain business performance indicates the overall success of the supply chain employees. One of the employee performances is OCB since OCB has interpersonal impacts. The research results show that supply chain employees with transformational supply chain leaders have higher measure values in organizational citizenship behavior (OCB). Using the Rasch Model Approach, it is proven transformational supply chain leaders can be a leadership strategy in creating supply chain business performance.